Powder spreading effects on laser powder bed fused parts quality - Fatima-Ezzahrae Jabri; Aissa Ouballouch; Larbi Lasri; Rachid El Alaiji (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Laser powder bed fusion (LPBF) is an additive manufacturing technique whose efficiency and quality depend largely on a consistent and precise powder spreading procedure. This article examines the crucial role of powder spreading in influencing the quality of 3D-printed parts. Through case studies and experimental results, the article demonstrates in detail the impact of parameters such as: powder flowability, spreading speed, layer thickness, and recoater type on powder uniformity during spreading. In addition, the paper presents a comparison between types of recoaters in order to obtain optimum surface finish, mechanical properties, and reduced defects. This paper reviews the most appropriate powder spreading techniques to maintain the flowability and uniformity of the powder. Therefore, the primary objective of this work is to present an in-depth review of the impact of powder spreading dynamics in LPBF. In addition, it aims to demonstrate to the reader the various factors influencing powder spreading and the methodologies employed to optimize this crucial process.